Epidural Anaesthesia Technique in Caesarean Section Operation in Pregnant Patients with Rheumatic Heart Disease and Severe Mitral Stenosis - Wangsa, Aditya; FX Adinda Putra Pradhana; Tjahya Aryasa EM; Cynthia Dewi Sinardja (Journal of Anesthesiology and Clinical Research, 2023)
Introduction: Mitral stenosis (MS) is the most common form of rheumatic heart disease (RHD). Pregnant women with moderate/severe MS are more prone to heart failure and pulmonary edema than normal pregnant women. It is very important to prevent the potential for maternal heart failure before delivery. This study aimed to present a case report on the epidural anaesthesia technique in caesarean section in pregnant patients with rheumatic heart disease and severe mitral stenosis. Case presentation: A 31-year-old pregnant woman patient came to the hospital with complaints of shortness of breath and found rheumatic heart disease and severe mitral stenosis. The patient was premedicated with fentanyl 50 mcg and midazolam 1 mg intravenously, followed by oxygen supplementation with a 2 lpm nasal cannula. Anaesthesia was performed using a lumbar epidural technique, with the insertion of an epidural catheter in the L1-L2 intervertebral space, targeting the T10-L1 dermatome and T6-L1 target of the viscerotome. The local anaesthesia agent chosen was plain bupivacaine with a concentration of 0.5% and a volume of 25 ml. The onset of action of epidural anaesthesia is achieved within 15 minutes as long as the operation is reached a total blockade as high as T6. During surgery, the patient is monitored with standard monitors and an artery line. There were no complaints of shortness of breath felt by the patient during the operation. Conclusion: Epidural anaesthesia technique can be performed safely in pregnant women with comorbid mitral regurgitation and atrial fibrillation, with good intraoperative hemodynamic stability.